Comparative mitogenome analysis of two ectomycorrhizal fungi (Paxillus) reveals gene rearrangement, intron dynamics, and phylogeny of basidiomycetes - Qiang Li; Yuanhang Ren; Dabing Xiang; Xiaodong Shi; Jianglin Zhao; Lianxin Peng; Gang Zhao (IMA Fungus)
Abstract In this study, the mitogenomes of two Paxillus species were assembled, annotated and compared. The two mitogenomes of Paxillus involutus and P. rubicundulus comprised circular DNA molecules, with the size of 39,109 bp and 41,061 bp, respectively. Evolutionary analysis revealed that the nad4L gene had undergone strong positive selection in the two Paxillus species. In addition, 10.64 and 36.50% of the repetitive sequences were detected in the mitogenomes of P. involutus and P. rubicundulus, respectively, which might transfer between mitochondrial and nuclear genomes. Large-scale gene rearrangements and frequent intron gain/loss events were detected in 61 basidiomycete species, which revealed large variations in mitochondrial organization and size in Basidiomycota. In addition, the insertion sites of the basidiomycete introns were found to have a base preference. Phylogenetic analysis of the combined mitochondrial gene set gave identical and well-supported tree topologies, indicating that mitochondrial genes were reliable molecular markers for analyzing the phylogenetic relationships of Basidiomycota. This study is the first report on the mitogenomes of Paxillus, which will promote a better understanding of their contrasted ecological strategies, molecular evolution and phylogeny of these important ectomycorrhizal fungi and related basidiomycete species.